Unveiling the biological activities of Heliotropium indicum L. plant extracts: anti-inflammatory activities, GC–MS analysis, and in-silico molecular docking - Mst. Sadia Afroz Shoily; Md. Ekramul Islam; Nur Mohammad Rasel; Shahnaz Parvin; Jaytirmoy Barmon; Aqibul Hasan Aqib; Debendra Nath Roy; Mst. Shahnaj Parvin (Scientific Reports)
Abstract Heliotropium indicum is well-known for its diverse medicinal properties, traditionally utilized to treat ailments such as diabetes, obesity, bacterial infections, inflammation, and diarrhea. This study aims to explore the anti-inflammatory effects of the extract using in vitro methods and to assess its drug-likeness potential using docking, PASS and ADME. Fractionations of crude methanol extract (CME) were undertaken in n-hexane (NHF), chloroform (CHF), and ethyl acetate (EAF). GC–MS analysis was conducted using Agilent technologies. All fractions were evaluated for radical scavenging and anti-inflammatory properties in vitro. Molecular docking was performed with PyRx and Biovia Discovery Studio, followed by drug-likeness analysis using Swiss ADME. The ethyl acetate fraction (EAF) showed the highest DPPH scavenging activity (IC50: 4.3 μg/ml), followed by chloroform (CHF, IC50: 12.95 μg/ml) and n-hexane fractions (NHF, IC50: 17.6 μg/ml). Catechin had an IC50 of 3.5 μg/ml. EAF and CHF also exhibited the highest hydroxyl radical scavenging activity (51.69 μg/ml). EAF demonstrated significant anti-inflammatory activity, inhibiting heat-induced hemolysis (71.90%), hypotonicity-induced hemolysis (67.18%), and AAPH-induced hemolysis (72.52%) at 400 μg/ml. Six major phytoconstituents in EAF, identified by GC–MS, were docked with COX-2. ADME and drug-likeness evaluations using the Lipinski’s “rule of five" confirmed all compounds had acceptable pharmacokinetic properties to fulfill the pharmaceutical formulations requirement. The study depicts the first and novel report of GC–MS compounds on in silico analysis. Both EAF and CHF exhibit significant anti-inflammatory activity, indicating their potential as a source for developing new therapeutic agents for treating inflammation.